Great Indian Economists-2 Their creative vision for socio-economic development -Mahadev Govind Ranade - Das, Debendra Kumar (ed) (New Delhi Deep & Deep Publications, 2004)
Mahadev Govind Ranade : life sketch and economic philosophy